2022
DOI: 10.5582/bst.2022.01251
|View full text |Cite
|
Sign up to set email alerts
|

Needs of cancer patients during the SARS-CoV-2 Omicron lockdown: A population-based survey in Shanghai, China

Abstract: The SARS-CoV-2/COVID-19 Omicron variant was first identified in November 2021 in Botswana and South Africa (1). Although immunological and clinical data did not provide definitive evidence, the omicron variant displayed early signs of high transmissibility, reduced severity, and immune escape, potentially increasing the difficulty of controlling the pandemic (2,3). In late February 2022, a wave of omicron BA.2 infection rapidly appeared in Shanghai, China. Shanghai is one of the most important international ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Pressure on patients and healthcare providers, institutions, and systems imposed by the COVID-19 pandemic has been repeatedly and widely reported, both in China and worldwide 16 , 23 , 24 . Our findings regarding unmet needs in healthcare services during the lockdown in Shanghai are consistent with previously published estimates 10 , 25 , 26 . Several reasons have been cited for declining healthcare utilization during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pressure on patients and healthcare providers, institutions, and systems imposed by the COVID-19 pandemic has been repeatedly and widely reported, both in China and worldwide 16 , 23 , 24 . Our findings regarding unmet needs in healthcare services during the lockdown in Shanghai are consistent with previously published estimates 10 , 25 , 26 . Several reasons have been cited for declining healthcare utilization during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…To reduce the spread of the pandemic, Shanghai announced a phased lockdown in late March followed by a city-wide lockdown beginning on April 3. Mitigation measures included movement restrictions, home confinement, and suspension of all non-essential production and commercial activities 9 , 10 . The lockdown in Shanghai—China’s most populous city—represented the most extensive lockdown since the Wuhan shutdown in the initial phase of the pandemic in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study highlighted a significant concern among family caregivers regarding the nutritional status of patients with cancer, which was at times compromised due to supply issues during the lockdown in Shanghai. Like other work emphasised the importance of nutrition needs of patients with cancer during the lockdown (Chen et al, 2022), this study also suggested that the unmet food and nutrition needs of patients with cancer was one of the most significant factors contributing to family caregivers' stress during the same period. Family caregivers' feelings may reflect not only their concerns about the biological and medical needs of patients with cancer, but also a shared belief worldwide as well as is evident in Chinese culture that providing nutritious food is an expression of love, caring and filial piety.…”
Section: Discussionsupporting
confidence: 68%
“…Although a few studies have investigated the needs and psychosocial concerns of patients with cancer during the COVID‐19 crisis (Chen et al, 2022; Xu et al, 2022), little is known about the experience of family caregivers supporting their significant others during the lockdown period. With many patients with cancer being immunocompromised, the pandemic might add concerns for both the patients and their family caregivers about increasing risks of contraction and severe consequences that could follow when they were confined in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were identified and recruited based on their health status at follow-up visits in the past year. The patient is in a stable survivorship phase and is not in urgent need of surgery or radiotherapy ( 29 ). The study received ethical approval from the Shanghai Health and Health Development Research Center (Shanghai Institute of Medical Science and Technology Information) under protocol number SHDRC2022005.…”
Section: Methodsmentioning
confidence: 99%